Komunikasi Antar Pribadi Guru Dan Siswa Dalam Memotivasi Belajar Siswa SMP Negeri 13 Bogor - Sartika, Rawit; Suratriadi, Panji; Diah Astuti, Fajar (Jurnal Public Relations (J-PR), 2023)
Communication is closely related to aspects of education, where education is a process of empowerment that explores human potential as individuals and society and has a function in addition to empowering human potential as well as developing and controlling this potential so that it is beneficial for improving the quality of the human being himself. In the educational aspect, of course, it cannot be separated from the role of educators, or teachers if in a school environment it is usually called a teacher. A teacher basically conducts outreach in the implementation of education. This socialization applies in learning activities, in order to increase student learning motivation. Reciprocal relationship between teachers and students will determine the end result of increased student motivation. The results of this study indicate that interpersonal communication between teachers and students in motivating student learning at SMP Negri 13 Bogor is carried out directly (face to face) or indirectly (through the media). The media used is WhatsApp social media. Through interpersonal communication the teacher tries to direct students to have a high interest in learning. Messages delivered persuasively, messages conveyed by the teacher are directed to achieve the goals to be achieved by students. Keywords: Interpersonal Communication, Teachers and Students, Learning Motivation